La traduction littéraire qui n’est pas que la traduction. Sur les enjeux traductologiques au Canada - Warmuzińska-Rogóż, Joanna (Romanica Silesiana, 2020)
The article aims to take a close look at the literary relations between English- and French-speaking Canada. Among different possibilities, the author analyzes specific cases concerning literary prizes, in particular winners of the Governor General’s Prize in the category of translation. As it is one of the most prestigious awards in Canada, it undoubtedly conditions the reception of a literary work, being a symbol of prestige. The choice of the jury can sometimes seem surprising or even confusing, as it was the case of Nancy Huston or Jacques Brault who won the prize in the category of translation. Without a doubt, the specificity of the translation à la canadienne goes beyond any distinctions and descriptions and – being also a political issue – revolts against all control and all interference.